Revisiting Major Historical Earthquakes in Nepal: Overview of 1833, 1934, 1980, 1988, 2011, and 2015 Seismic Events - Chaulagain, Hemchandra (2019)
Due to its location in the region of interaction between the Indian and Eurasian plates, several earthquakes hit Nepal each year. These shaking events, from weak to strong, characterize Himalayan earthquakes, and major events in the past caused enormous losses in terms of casualties, injuries, biodiversity, and the country’s economy. Due to lack of proper accounts related to the occurrence, damage, and losses of past earthquakes, few accounts of the 20th century earthquakes can be found in existing literature; and comparative analysis of these earthquakes has not been done. To fill this hiatus of detailed accounts and interpretation of notable earthquakes in Nepal, this chapter offers classified damage statistics, losses, and the impact on the socioeconomic setting of the affected areas. In addition, it presents the damage to gender, rural, and urban populations along with brief details of known earthquakes since 19th century.